THE EFFECT OF PICTURE WORD INDUCTIVE MODEL (PWIM) AND STUDENTS’ SELF-EFFICACY TOWARD THEIR WRITING SKILL OF DESCRIPTIVE TEXTS AT GRADE X OF SMA NEGERI 1 IX KOTO SUNGAI LASI - Sepyanda, Mariska (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2014)
This study was written to see the effect of picture strategy inductive model (PWIM) and student self-efficacy to their skills in writing descriptive text. This research is a quasi-experimental design with factorial design. This research data is taken from the result of student writing skill test and self-efficacy questionnaire. Then, the data were analyzed by using t-test and two-way Anova through Minitab 14 application. The results of this study indicate that PWIM strategy has a significant effect on students' writing skill when compared with listing strategy used by teachers in writing teaching. The result shows a t count of 1,900 which is larger than the t-table that is worth 1.684. Then, students with high self-efficacy taught with the PWIM strategy have a better ability to write descriptive text than students taught with a listing strategy, where t counts are 3.160 which is greater than t-tables of 1.812. However, students with low self-efficacy taught by the PWIM strategy do not have a better ability to write descriptive text than students taught by a listing strategy that t-counts 1.730 smaller than t-tables of 1.812 . Furthermore, from the results of the study also found that there is no interaction between teaching strategies with self-efficacy to the writing skills of students where F-count is 0.08 higher than the F-table is 2.58.